Роль Василя Стуса в боротьбі за незалежність України та розвиток її культури - Хая, А. О. (ХНУРЕ, 2022)
The aim of the work is to study the role of Vasyl Stus in the struggle for independence of Ukraine and the development of its culture. Vasyl Semenovych Stus devoted his entire life to the preservation and development of Ukrainian culture.